Modelling the decorative patterns of a Geometric oinochoe. An interpretative approach using chess-related terminology and metaphors - Christakopoulou, Gioulika (Journal of Greek Archaeology, 2023)
During an archaeological research conducted in Patras/Achaea in 2000 on a property owned by the company N. Giannopoulos - P. Angelopoulos, an ancient funerary road was discovered. This road, known from previous excavations, had a direction north-south and crossed the northern cemetery before continuing as a via publica that led to Aigion and Corinth. In the southern part of the property, a funerary enclosure (measuring 10.50 x 7.70 meters) was also found that may not have been directly connected to the ancient road. In the northwest internal corner of the enclosure, a rectangular chamber was discovered, which was contemporary with the funerary enclosure. During the excavation, thirteen tombs were investigated, including tile-roofed and built cist tombs from the later Roman period, as well as eight funerary urns.